Perspectives of Existing Storm Water Drainage in Pokhara - Shrestha, Kishor Kumar (Technical Journal, 2019)
Addressing issues of waste water is one of the key challenges in the context of Nepal. Being in the highest rainfall area, storm water management is even more crucial in Pokhara. Storm water drains were designed and constructed in Pokhara about two decades ago. Total 50 kilometer long storm water drains have been built which covers the core city area of Pokhara. The design considerations were based on the then available references. Much has been changed since that time and the present data will give different drain cross sections. Further, the concept of discharging storm water in to water bodies without making any pollution need to be reviewed in terms of quality aspects. Review of quantitative as well as qualitative features of the storm water drains could enhance its function more effectively.